A survey of mental health literacy in parents and guardians of teenagers - Kusaka, Sakurako; Foo, Jerome Clifford; Yamaguchi, Satoshi; Yukawa, Ayuko; Arai, Takuya; Sawamura, Fumika; Togo, Fumiharu; Sasaki, Tsukasa (Frontiers in Psychiatry, 2024)
Introduction: Parents and guardians (hereafter caregivers) of teenagers need high levels of mental health literacy (MHL) to manage mental health problems arising in teenagers in their care. Previous studies assessing MHL levels in caregivers of teenagers have reported mixed results, making it difficult to clearly estimate caregiver MHL levels. This study aimed to investigate MHL levels in Japanese caregivers of regular teenagers. Methods: Responses from caregivers (n = 1,397) of students entering junior and senior high schools to a self-administered online questionnaire were analyzed. The questionnaire assessed (a) knowledge about mental health/illnesses and (b) attitudes towards mental health problems in teens in their care (e.g., recognition of depression as a medical illness and intention to engage in helping behaviors). Results: The average proportion of correct answers to the knowledge questions (n = 7) was 55.4%; about one tenth (9.2%) of caregivers correctly answered only one or none of the questions. Few caregivers correctly answered about the life-time prevalence of any mental illnesses (46.1%) and appropriate sleep duration for teenagers' health (16.5%). The proportions of caregivers who had the intention to listen to the teen in their care, consult another person, and seek professional medical help if the teen suffered from depression were 99.5%, 91.5% and 72.7%, respectively. Conclusions: Many teenagers' caregivers appeared to be willing to help the teens in their care if they were suffering from mental health problems. However, there was much room for improvement in knowledge on mental health/illnesses and intention to seek help from medical professionals. Efforts toward better education should be made.